(untitled) (Global Journal of Medical Research, 2018)
This study evaluated the impact of simulated nitric acid rain (SNAR) and sulphuric acid rain (SSAR) on the nutrient status of Telfairia occidentalis. Results of phytochemical screening of T. occidentalis revealed the presence of alkaloids, saponins, flavonoids, reducing compounds, polyphenols in all parts with the absence of phlobatanins, anthraquinones and hydroxymethyl anthraquinones in aqueous and ethanol extracts of SNAR and SSAR as well as the control. Tannins, steroids, terpenoids, and glycosides were present in some plant parts and absent in others. Impact of simulated HNO3 and H2SO4 acid rain on qualitative phytochemicals resulted in significant (P=0.05) increase and adecrease in phytochemicals. Ash, protein, fat, fiber and carbohydrate showed decrease owing to SNAR and SSAR impact with an increase in root fat content. Protein was significantly reduced at all levels of acidity with leaf percentage reduction of 54.3%, 37.7%, 20.3% and 62.0%, 42.6%, 10.4% for SNAR and SSAR at pH 2.0, 3.0, and 4.0 respectively. Impact of SNAR and SSAR causedadecrease inhistidine, isoleucine, leucine, lysine, methionine, phenylalanine, threonine, tryptophan, valine, alanine, arginine, cysteine, glycine, serine, tyrosine with anincrease in glutamic acid, aspartic acid, proline, and alanine. K, Na, Ca, Mg, Mn, Cu, Zn, Fe, and P were also reduced.